Analysis of The Influence of Work Environment, Job Satisfaction and Work Load on Employee Performance at the East Belitung District Health Office - Ahmad Zainuddin; Dewi Yustiana; Sari Handayani; Siti Nur Soleha (PT FORMOSA CENDEKIA GLOBAL, 2024)
The extent to which an employee contributes to the organization they work for typically determines the success of that organization. In certain businesses, one of the main factors influencing a company's success is employee performance. The level of productivity that you desire is contingent upon the performance of your employee. The purpose of this study was to determine whether there is an effect of work environment, job satisfaction, and workload on employee performance at the Belitung Timur District Health Office. Either simultaneously, partially, or dominantly. So that the research can be taken into consideration for the Health Office of East Belitung Regency to understand what factors can affect the Employee Performance of the East Belitung Regency Health Office. Based on the study's findings, it was determined that the independent factors had a significant impact on the dependent variable, either concurrently or partially. Based on the study's findings, workload is the major variable. Based on the test results, the independent variable's contribution to the dependent variable is explained by the R square value of 91.9%.